Magnesium phosphate-based cement grouting material as well as preparation method and application thereof
By using magnesium phosphate-based cement grouting materials and using components such as calcined magnesium oxide and bentonite, the problems of long settling time and poor water dispersion inorganic grouting materials are solved, and the effect of rapid repair of underground leaked water cracks is achieved, and the advantages of low shrinkage, short settling time and high compressive strength are achieved.
Patent Information
- Application Number
- CN202411927163.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the prior art, inorganic grouting materials have long settling time, poor water dispersion resistance, complex construction, and poor durability in long-term soaking environments, making it difficult to quickly and effectively repair leaky cracks in underground projects.
Magnesium phosphate-based cement grouting materials are used, and their raw materials include calcined magnesium oxide, bentonite, hydroxypropyl methylcellulose, pretreated polymer water-absorbing resin and dihydrogen phosphate, etc. Through specific component ratios and treatment methods, grouting materials with low shrinkage, short settling time, high compressive strength, simple construction, low cost and green and environmentally friendly are prepared.
It achieves the effect of short condensation time and adjustable, high compressive strength, simple construction, low cost and green environmental protection, good slurry injection, good water dispersion, and good durability in long-term soaked water environments. It is suitable for rapid repair of leaky cracks in underground projects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting materials, and in particular to a magnesium phosphate-based cement grouting material and a preparation method and application thereof. Background Art
[0002] With the rapid economic development and the shortage of land resources in my country, underground engineering construction has developed rapidly. However, water leakage is prone to occur in the construction of underground engineering represented by tunnels and stations, which endangers the safety, stability, durability of buildings (structures) and affects the normal use function, bringing huge operation and maintenance costs. Underground engineering leakage can be divided into slow seepage, fast seepage, water leakage and water gushing according to the flow rate. Among them, water leakage, especially strong seepage, is the most serious hazard. In engineering, epoxy resin, cement, cement-water glass materials and other materials are usually used to quickly solidify to form a gel structure for grouting and plugging. However, epoxy resin materials are expensive, environmentally unfriendly, and have poor resistance to water erosion; ordinary cement-based grouting materials have a long setting time, poor water resistance and dispersion, and are relatively complicated to construct; cement-water glass and other materials have a short gel time and high strength, but poor durability in a long-term water environment.
[0003] Chinese patent CN 117865593 A discloses a "new type of green anti-dispersion synchronous grouting material for water-rich formations and its preparation method", which is composed of the following components according to specific weight parts: silicate cement, fine sand, fly ash, hydroxypropyl methylcellulose, 2-ethylhexyl phosphate-2-ethylhexyl ester, sodium tripolyphosphate, sodium dodecyl sulfate, polycarboxylic acid superplasticizer or naphthalene superplasticizer, polyacrylamide, formic acid, bentonite, water. However, the setting time of this product is relatively long, and the initial setting time is 5 hours, which is not suitable as a rapid emergency repair material for leaking cracks. Chinese patent CN 108002802 A discloses "a phosphorus-magnesium-based cement grouting material and its preparation method", which is composed of the following components according to specific weight parts: composite magnesium compound, composite retarder, water reducer, acid-base buffer, composite stabilizer, composite surfactant, phosphate, defoamer. However, the water-cement ratio of this material is relatively small, and it is not suitable for grouting and water blocking conditions of tiny cracks.
[0004] Therefore, it is of great significance to develop a leakage crack repair material with short and adjustable setting time, high compressive strength, simple construction, low cost and green environmental protection, good slurry injectability, good water dispersibility, and good durability in long-term water immersion environment. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, propose a magnesium phosphate-based cement grouting material and its preparation method and application, and solve the technical problems of inorganic grouting materials in the prior art, such as long setting time, poor water dispersibility, complex construction, and poor durability in a long-term water immersion environment.
[0006] In a first aspect, the present invention provides a magnesium phosphate-based cement grouting material, the raw materials of which include component A and component B; wherein, by weight, the raw materials of component A include: 140-200 parts of calcined magnesium oxide, 0-30 parts of bentonite, 0.2-0.5 parts of hydroxypropyl methylcellulose, 1-10 parts of an admixture and 70-140 parts of water; the raw materials of component B include: 70-100 parts of a first dihydrogen phosphate, 20-50 parts of a pretreated polymer water-absorbing resin, 0.5-2 parts of sodium polyacrylate and 30-70 parts of water; the pretreated polymer water-absorbing resin is obtained by immersing the polymer water-absorbing resin in an aqueous solution of a second dihydrogen phosphate; the molar ratio of magnesium to phosphorus in the calcined magnesium oxide and the first dihydrogen phosphate is (5.5-6.5):1.
[0007] In a second aspect, the present invention provides a method for preparing a magnesium phosphate-based cement grouting material, comprising the following steps: The calcined magnesium oxide, bentonite and hydroxypropyl methylcellulose are mixed evenly to obtain a mixed powder; the admixture and water are mixed evenly to obtain a mixed liquid; the mixed powder and the mixed liquid are mixed evenly to obtain component A; The first dihydrogen phosphate, sodium polyacrylate, pretreated high molecular water-absorbent resin and water are uniformly mixed to obtain component B.
[0008] In a third aspect, the present invention provides an application of a magnesium phosphate-based cement grouting material, wherein the magnesium phosphate-based cement grouting material is applied to sealing water leakage cracks.
[0009] Compared with the prior art, the beneficial effects of the present invention include: The magnesium phosphate-based cement grouting material of the present invention has the characteristics of low shrinkage, short and adjustable setting time, high compressive strength, simple construction, low cost and green environmental protection, good slurry injectability, good water resistance and dispersibility, and good durability in a long-term water immersion environment. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0011] In a first aspect, the present invention provides a magnesium phosphate-based cement grouting material, whose raw materials include component A and component B; wherein, by weight, the raw materials of component A include: 140-200 parts of calcined magnesium oxide, 0-30 parts of bentonite, 0.2-0.5 parts of hydroxypropyl methylcellulose, 1-10 parts of an admixture and 70-140 parts of water; the raw materials of component B include: 70-100 parts of a first dihydrogen phosphate, 20-50 parts of a pretreated high molecular water-absorbing resin, 0.5-2 parts of sodium polyacrylate and 30-70 parts of water.
[0012] The functions of the main raw materials used in the present invention are as follows: Magnesium oxide and ammonium dihydrogen phosphate: The two react to form a cementing phase struvite, which together with dead-burned magnesium oxide (aggregate function) provides strength; magnesium oxide is both a raw material for forming a cementing phase struvite and an aggregate for magnesium phosphate (MPC) cement. Lightly burned magnesium oxide with a low calcination temperature provides a faster reaction rate, while dead-burned magnesium oxide with a high calcination temperature provides an aggregate function; Bentonite and hydroxypropyl methylcellulose: can increase the viscosity of component A, improve the stability of component A and avoid sedimentation; Pre-treated polymer water-absorbent resin (SAP): obtained by pre-adsorbing dihydrogen phosphate solution on polymer water-absorbent resin. By adopting the above-mentioned pre-treated SAP, not only the proportion of actual dihydrogen phosphate can be increased, but also a similar internal curing effect can be played. The dihydrogen phosphate is slowly released and the struvite generated by the reaction with magnesium oxide in the later stage can fill the gaps. The exothermic reaction of magnesium oxide and dihydrogen phosphate in the early stage can make the pre-treated polymer water-absorbent resin release dihydrogen phosphate to further participate in the reaction, extend the total reaction time, and make the reaction relatively mild; the polymer water-absorbent resin that releases dihydrogen phosphate solution in the later stage can absorb a small amount of water immersed in the grouting material to a certain extent and expand to fill the gaps, hindering water transmission and improving the material's resistance to water erosion.
[0013] Sodium polyacrylate: In aqueous solution, the molecular chains of sodium polyacrylate can form a network structure, and these molecular chains have a certain cross-linking effect, which can increase viscosity and improve water dispersibility; at the same time, the molecular chains contain hydrophilic carboxyl functional groups, which will produce carboxylate anions after being neutralized by alkali, and have good acid and alkali resistance.
[0014] In this embodiment, the first dihydrogen phosphate is at least one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, and sodium dihydrogen phosphate, preferably ammonium dihydrogen phosphate. Among the above dihydrogen phosphates, ammonium dihydrogen phosphate reacts fastest with magnesium oxide and has the highest early strength, which can meet the requirements of rapid plugging and provide higher early strength, so ammonium dihydrogen phosphate is preferred.
[0015] In this embodiment, the pretreated polymer water-absorbent resin is obtained by immersing the polymer water-absorbent resin in an aqueous solution of a second dihydrogen phosphate.
[0016] The particle size of the polymer water-absorbent resin is 200-500 meshes, the water absorption rate in pure water is 100-1000 times, and the liquid absorption rate in 2.5 mol / L dihydrogen phosphate solution is 1-50 times.
[0017] The second dihydrogen phosphate is at least one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, and sodium dihydrogen phosphate. Among the above dihydrogen phosphates, ammonium dihydrogen phosphate reacts fastest with magnesium oxide and has the highest early strength, which can meet the requirements of rapid plugging and provide higher early strength, so ammonium dihydrogen phosphate is preferred.
[0018] The concentration of the aqueous solution of the second dihydrogen phosphate is 1-5 mol / L, and further 2.5 mol / L.
[0019] The solid-liquid ratio of the polymer water-absorbent resin to the aqueous solution of the second dihydrogen phosphate is 1:(50-500), and further 1:100.
[0020] The soaking temperature is 20-30°C, the soaking time is 10-60min, and further 10min.
[0021] The pretreated polymer water-absorbent resin is obtained by adsorbing the polymer water-absorbent resin to saturation in an aqueous solution of a second dihydrogen phosphate.
[0022] In this embodiment, the magnesium oxide is at least one of light-burned magnesium oxide or dead-burned magnesium oxide.
[0023] Preferably, the calcination temperature of light-burned magnesium oxide is 900-1000°C, further 950°C; the calcination temperature of heavy-burned magnesium oxide is 1600-1700°C, further 1650°C.
[0024] Preferably, the calcined magnesium oxide is compounded by light-burned magnesium oxide and dead-burned magnesium oxide. Generally speaking, the lower the calcination temperature, the higher the activity of magnesium oxide, and the faster it participates in the reaction; the higher the calcination temperature, the higher the strength of magnesium oxide, which acts as an aggregate and can provide higher strength. In the compounding system of the present invention, the light-burned magnesium oxide reacts first and provides strength faster. After the light-burned magnesium oxide reacts, the dead-burned magnesium oxide continues to react. After the dihydrogen phosphate reaction is completed, the remaining magnesium oxide is magnesium oxide with a higher calcination temperature, which can provide a higher strength for the matrix. The compounding of the two can achieve rapid plugging while achieving relatively high strength.
[0025] More preferably, the mass ratio of light-burned magnesium oxide to dead-burned magnesium oxide is (2-4):1, more preferably 3:1.
[0026] In this embodiment, the particle size of the bentonite is 100-300 mesh, and further is 200 mesh.
[0027] In this embodiment, the viscosity of hydroxypropyl methylcellulose is 100,000-300,000 mPa·s, and further 200,000 mPa·s.
[0028] In this embodiment, the additive includes at least one of a defoaming agent and a water reducing agent.
[0029] Wherein, the defoaming agent is a silicone defoaming agent, and the solid content is 5%-20%, and further 10%.
[0030] Among them, the water reducer is a high-efficiency polycarboxylic acid water reducer with a solid content of 30%-50%, and further 40%.
[0031] In this embodiment, the molar ratio of magnesium to phosphorus in the calcined magnesium oxide and the first dihydrogen phosphate is (5.5-6.5):1, further 6:1.
[0032] In this embodiment, the magnesium phosphate-based cement grouting material, by weight, the raw materials of component A include: 170-190 parts of calcined magnesium oxide, 15-20 parts of bentonite, 0.3-0.4 parts of hydroxypropyl methylcellulose, 3-6 parts of admixtures and 100-120 parts of water; the raw materials of component B include: 80-90 parts of first dihydrogen phosphate, 30-40 parts of pretreated high molecular water-absorbing resin, 0.8-1.2 parts of sodium polyacrylate and 40-60 parts of water.
[0033] In a second aspect, the present invention provides a method for preparing a magnesium phosphate-based cement grouting material, comprising the following steps: S1. Evenly mix calcined magnesium oxide, bentonite and hydroxypropyl methylcellulose to obtain a mixed powder; evenly mix an admixture and water to obtain a mixed liquid; evenly mix the mixed powder and the mixed liquid to obtain component A; S2. Evenly mix the first dihydrogen phosphate, sodium polyacrylate, pretreated polymer water-absorbent resin and water to obtain component B.
[0034] The present invention does not limit the order of steps S1 and S2, and those skilled in the art may select the order according to actual conditions.
[0035] In this embodiment, the calcined magnesium oxide, bentonite and hydroxypropyl methylcellulose are uniformly mixed by stirring, and the stirring time is 20-60 seconds.
[0036] In this embodiment, the additive and water are mixed uniformly by stirring, and the stirring time is 20-60s.
[0037] In this embodiment, the mixed powder and the mixed liquid are mixed evenly by stirring, and the stirring time is 1-5 minutes.
[0038] In this embodiment, the first dihydrogen phosphate, sodium polyacrylate, pretreated polymer water-absorbing resin and water are uniformly mixed by stirring for 0.5-2 minutes.
[0039] In a third aspect, the present invention provides an application of a magnesium phosphate-based cement grouting material, wherein the magnesium phosphate-based cement grouting material is applied to plugging water seepage cracks, preferably to plugging strong water seepage cracks.
[0040] In this implementation, the above-mentioned applications include: Mix component A and component B evenly and inject them into leaking cracks for sealing.
[0041] Furthermore, the process of uniformly mixing component A and component B includes: loading component A and component B into a slurry storage bin of a double-liquid grouting machine, and uniformly mixing component A and component B by the double-liquid grouting machine.
[0042] To avoid redundant description, some raw materials in the following embodiments and comparative examples of the present invention are summarized as follows: Magnesium oxide: Both light-burned magnesium oxide and dead-burned magnesium oxide are provided by Dashiqiao Jubo High Temperature Refractory Material Business Department. The calcination temperature of light-burned magnesium oxide is 950 °C and the specific surface area is 1.62 m 2 / g, purity is 85.98%; dead-burned magnesium oxide is calcined at 1650 °C, with a specific surface area of 1.35 m 2 / g, purity is 89.61%, chemical composition is shown in Table 1.
[0043] Table 1 Chemical composition of magnesium oxide / wt.%
[0044] The particle size of bentonite is 200 mesh; The viscosity of hydroxypropyl methylcellulose is 200,000 mPa·s; The defoamer is a silicone defoamer with a solid content of 10%; The water reducer is a high-efficiency polycarboxylate water reducer with a solid content of 40%; Ammonium dihydrogen phosphate was analytically pure; The pretreated polymer water-absorbent resin is obtained by the following method: the polymer water-absorbent resin is pre-immersed in a 2.5 mol / L diammonium phosphate solution at 25°C for 10 min, with a solid-liquid ratio of 1:100; the particle size of the polymer water-absorbent resin is 400 mesh, the water absorption rate in pure water is 500 times, and the liquid absorption rate in the 2.5 mol / L diammonium phosphate solution is measured to be 8.6 times.
[0045] Examples 1-6 and Comparative Examples 1-4 The preparation method of the magnesium phosphate-based cement grouting material provided in Examples 1-6 and Comparative Examples 1-4 comprises the following steps: (1) Preparation of component A: Weigh a certain amount of calcined magnesium oxide, bentonite, and hydroxypropyl methylcellulose according to the proportions in Tables 2 and 3, and stir for 30 seconds until the raw materials are fully mixed; weigh a certain amount of water reducer, defoamer, and water according to the proportions in Tables 2 and 3, and stir for 30 seconds until they are fully mixed; mix the powder and liquid and stir for 2 minutes to form component A.
[0046] (2) Preparation of component B: According to the mixing ratios in Tables 2 and 3, a certain amount of ammonium dihydrogen phosphate, sodium polyacrylate, pretreated polymer water-absorbing resin (comparative example 2 is a polymer water-absorbing resin), and water were weighed and stirred for 1 min until fully mixed to form component B.
[0047] Comparative Example 5 (cement-water glass system) The preparation method of cement-water glass double liquid grouting material comprises the following steps: (1) Preparation of component A: Weigh a certain mass of cement according to the mix ratio in Table 4, weigh a certain mass of polycarboxylic acid water reducer, silicone defoamer and water according to the mix ratio in Table 4, and stir for 30 seconds until fully mixed; mix the powder and liquid and stir for 2 minutes to form component A.
[0048] (2) Preparation of component B: Weigh a certain mass of sodium silicate (40° Baume) and water according to the mix ratio in Table 4 and stir for 2 minutes to form component B.
[0049] Table 2 Grouting material formula used in Examples 1-6 and Comparative Examples 1-4 (parts by weight)
[0050] Table 3 Formula of calcined magnesium oxide used in Examples 1-6 and Comparative Examples 1-4 (parts by weight)
[0051] Among them, Examples 1-5 verify the influence of the ratio of calcined magnesium oxide on the new phosphate-magnesium-based cement grouting plugging material; Example 6 and Comparative Examples 1-4 respectively verify the influence of bentonite, polymer water-absorbent resin and sodium polyacrylate on the new phosphate-magnesium-based cement grouting plugging material.
[0052] Table 4 Grouting material formula used in Comparative Example 5 (parts by weight)
[0053] Performance Testing The A component and the B component of the above grouting material were mixed evenly, and injected into a 40*40*160 mm mold by air molding and underwater molding. The mold was demolded after 0.5 h, and the molds were cured in air and water respectively. The curing system in air was 20±2 ℃ and the relative humidity was ≥95%, and the curing system in water was 20±2 ℃. After 28 days, the compressive strength was measured and the water-land strength ratio was calculated.
[0054] The underwater stone rate HR is the ratio of the volume of underwater formed stones to the initial volume of the slurry. Use a syringe to extract 100 ml of the newly mixed slurry and inject it into a container containing 100 ml of water. After 3 hours, measure the volume of water and un-stoned slurry. The formula for calculating the stone rate HR of the sample is: HR = (V 浆 +V 水 -V0) / V 浆 ×100% (1) V 浆 ——The volume of the newly mixed grouting liquid, take 100 ml; V 水 ——The volume of water injected, take 100 ml; V0——the volume of remaining water and unformed slurry after 3 h.
[0055] The retention rate of slurry against dynamic water scour was tested using the slurry anti-scour performance test device built by the laboratory. The dynamic water tank is 200 cm long, 15 cm wide and 5 cm high. The water flow rate is controlled to be 0.4 m / s by adjusting the water inlet valve. 500 g of slurry is injected each time, recorded as M0, and poured directly into the test plate 20 cm away from the water inlet to simulate the grouting process. The injection process is maintained at a constant speed. When clear water continues to flow out of the outlet, the mass of the remaining slurry on the test plate is measured, recorded as M1, and the slurry retention rate, i.e. GRR (grout retention ratio), is calculated. The calculation formula for the retention rate of slurry against dynamic water scour is: GRR=M1 / M0×100%(2) The test results are shown in Table 5.
[0056] Table 5 Performance test results of Examples 1-6 and Comparative Examples 1-5
[0057] Please refer to Table 5. It can be seen from Table 5 that compared with Comparative Example 5, the magnesium phosphate-based cement grouting materials prepared in Examples 1-6 of the present invention all have lower setting time, higher 3h underwater stone rate, higher 28d underwater compressive strength, 28d water-to-land strength ratio and equivalent or even higher resistance to dynamic water erosion retention rate, which indicates that the magnesium phosphate-based cement grouting material of the present invention has the advantages of low shrinkage, short and adjustable setting time, high compressive strength, simple construction, low cost and green environmental protection, good slurry injectability, high impermeability, good water dispersibility and good durability in a long-term water immersion environment.
[0058] Examples 1-5 mainly verify the effect of calcined magnesium oxide on the new type of phosphorus-magnesium-based cement grouting plugging material. It can be seen from Examples 1-5 that with the increase of the weight ratio, the setting time gradually decreases and the 3h underwater stone rate gradually increases, but the 28d underwater compressive strength, 28d water-to-land strength ratio and the retention rate against dynamic water scouring all show a trend of first increasing and then decreasing.
[0059] Compared with Example 3, bentonite was not added in Example 6, and its 3h underwater stone formation rate, 28d underwater compressive strength, 28d water-to-land strength ratio and resistance to dynamic water erosion retention rate all decreased, but they were all significantly better than the existing cement-water glass system.
[0060] Compared with Example 3, in Comparative Example 1, no pre-treated high molecular water-absorbent resin was added, and its 3h underwater stone rate, 28d underwater compressive strength, 28d water-to-land strength ratio and resistance to dynamic water erosion retention rate all decreased, but were significantly better than the existing cement-water glass system.
[0061] Compared with Example 3, in Comparative Example 2, the pretreated high molecular water-absorbent resin is replaced with a high molecular water-absorbent resin, and the content of dihydrogen phosphate is increased. The dihydrogen phosphate in the system directly reacts with magnesium oxide, the coagulation time is shortened, the reaction rate is too fast, cracks appear in the sample, and its 28d underwater compressive strength, 28d water-to-land strength ratio, and resistance to dynamic water scouring are significantly reduced.
[0062] Compared with Example 3, in Comparative Example 3, no sodium polyacrylate was added, and its 3h underwater stone rate, 28d underwater compressive strength, 28d water-to-land strength ratio and resistance to dynamic water scouring were significantly reduced. Its water-to-land strength ratio and resistance to dynamic water scouring were even lower than those of the existing cement-water glass system.
[0063] Compared with Example 3, no bentonite, SAP and sodium polyacrylate were added to Comparative Example 4. Although its setting time was reduced, the 3h underwater stone rate, 28d underwater compressive strength, 28d water-to-land strength ratio and resistance to dynamic water scouring were significantly reduced. Its water-to-land strength ratio and resistance to dynamic water scouring were even lower than those of the existing cement-water glass system.
[0064] Compared with the prior art, the beneficial effects of the present invention mainly include: (1) High early strength, good late strength development, short and adjustable setting time, excellent water dispersibility, can quickly repair cracks, and has strong bonding properties.
[0065] (2) The raw materials are stable, easy to store, green and environmentally friendly, and the construction process is simple.
[0066] (3) Use different calcined magnesium oxides in combination, so that magnesium oxides with different calcination temperatures react in stages in the early stage (within a few minutes). This can not only participate in the reaction as quickly as possible to generate hydration products to provide initial strength, but also prevent the initial reaction from being too intense, resulting in a large amount of heat release and cracking of the grouting material matrix.
[0067] (4) Bentonite and lightly burned magnesium oxide provide magnesium phosphate cement with relatively high water absorption and expansion properties; pretreatment of SAP can reduce the reaction rate and improve the water resistance and water dispersibility of the material. Water absorption allows the slurry to absorb part of the water in the leakage cracks during the grouting process, reducing the difficulty of grouting and achieving better grouting results; expansion allows the underwater stone setting rate of this material to reach more than 100% within 3 hours, preventing the recurrence of cracks caused by shrinkage.
[0068] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A magnesium phosphate-based cement grouting material, characterized in that: The raw materials include component A and component B; wherein, by weight, the raw materials of component A include: 140-200 parts of calcined magnesium oxide, 0-30 parts of bentonite, 0.2-0.5 parts of hydroxypropyl methylcellulose, 1-10 parts of additives and 70-140 parts of water; the raw materials of component B include: 70-100 parts of first dihydrogen phosphate, 20-50 parts of pretreated high molecular water-absorbing resin, 0.5-2 parts of sodium polyacrylate and 30-70 parts of water; the pretreated high molecular water-absorbing resin is obtained by immersing the high molecular water-absorbing resin in an aqueous solution of a second dihydrogen phosphate; the molar ratio of magnesium to phosphorus in the calcined magnesium oxide and the first dihydrogen phosphate is (5.5-6.5):
1.
2. The magnesium phosphate-based cement grouting material according to claim 1, characterized in that: The magnesium oxide is at least one of light-burned magnesium oxide or dead-burned magnesium oxide; wherein The calcination temperature of the light-burned magnesium oxide is 900-1000°C; The calcination temperature of the dead-burned magnesium oxide is 1600-1700°C.
3. The magnesium phosphate-based cement grouting material according to claim 2, characterized in that: The calcined magnesium oxide is compounded by light-burned magnesium oxide and dead-burned magnesium oxide; wherein, The mass ratio of the light-burned magnesium oxide to the dead-burned magnesium oxide is (2-4):
1.
4. The magnesium phosphate-based cement grouting material according to claim 3, characterized in that: The mass ratio of the light-burned magnesium oxide to the dead-burned magnesium oxide is 3:
1.
5. The magnesium phosphate-based cement grouting material according to claim 1, characterized in that: The first dihydrogen phosphate and the second dihydrogen phosphate are at least one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, and sodium dihydrogen phosphate.
6. The magnesium phosphate-based cement grouting material according to claim 1, characterized in that: The particle size of the polymer water-absorbent resin is 200-500 mesh, the water absorption rate in pure water is 100-1000 times, and the liquid absorption rate in 2.5 mol / L dihydrogen phosphate solution is 1-50 times; and / or, The concentration of the aqueous solution of the second dihydrogen phosphate is 1-5 mol / L; and / or, The solid-liquid ratio of the polymer water-absorbent resin to the aqueous solution of the second dihydrogen phosphate is 1:(50-500); and / or, The soaking temperature is 20-30° C., and the soaking time is 10-60 min.
7. The magnesium phosphate-based cement grouting material according to claim 1, characterized in that: The particle size of the bentonite is 100-300 mesh; and / or, The viscosity of the hydroxypropyl methylcellulose is 100000-300000 mPa·s; and / or, The additive includes at least one of a defoamer and a water reducing agent.
8. The magnesium phosphate-based cement grouting material according to claim 1, characterized in that: The magnesium phosphate-based cement grouting material comprises, by weight, raw materials of component A including: 170-190 parts of calcined magnesium oxide, 15-20 parts of bentonite, 0.3-0.4 parts of hydroxypropyl methylcellulose, 3-6 parts of admixture and 100-120 parts of water; and raw materials of component B including: 80-90 parts of first dihydrogen phosphate, 30-40 parts of pretreated high molecular water-absorbing resin, 0.8-1.2 parts of sodium polyacrylate and 40-60 parts of water.
9. A method for preparing the magnesium phosphate-based cement grouting material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The calcined magnesium oxide, bentonite and hydroxypropyl methylcellulose are mixed evenly to obtain a mixed powder; the admixture and water are mixed evenly to obtain a mixed liquid; the mixed powder and the mixed liquid are mixed evenly to obtain component A; The first dihydrogen phosphate, sodium polyacrylate, pretreated high molecular water-absorbent resin and water are uniformly mixed to obtain component B.
10. An application of the magnesium phosphate-based cement grouting material according to any one of claims 1 to 8, characterized in that: The magnesium phosphate-based cement grouting material is used for sealing water leakage cracks.
Citation Information
Patent Citations
Novel green dispersion-resistant synchronous grouting material for water-rich stratum and preparation method of novel green dispersion-resistant synchronous grouting material
CN117865593A
Novel phosphorus and magnesium based cement grouting material and preparation method
CN108002802A
Degradable phosphate cement-based aggregate with fertilizer efficiency slow-releasing property and preparation method thereof
CN109987916A
Rapid pavement repairing mortar compounded with magnesium cement and alkali-activated slag and preparation method of rapid pavement repairing mortar
CN117800702A
Double-liquid grouting slurry, its technology and application for super large diameter underwater shield engineering under high water pressure condition
US20230212076A1
Cited By
Magnesium phosphate-based underwater pouring cementing material and preparation method thereof
CN120698717A